Millennial Employees Perception Of The Influence Of Transformational Leadership On Organizational Performance Through The Implementation Of Total Quality Management (TQM) Empirical Study at PT Asabri (Persero) Branch Offices - Novia Maharani Yuliana Dewi Putri Sari; Andriyani Andriyani (PT. Publikasiku Academic Solution, 2023)
This study aims to analyze the influence of transformational leadership on organizational performance through the implementation of TQM according to the perception of millennial employees at PT ASABRI (Persero) Branch Offices. Organizational performance is a characteristic that describes the quality of the organization that can be achieved with invaluable results. In achieving optimal organizational performance, the role of a leader is needed. Transformational leadership is considered capable of motivating team members to perform above average. In addition, a system such as total quality management (TQM) is also needed that is well implemented so that organizational performance is consistent with the goals that have been set. Organizational performance is measured by a balanced scorecard (BSC) approach, TQM implementation is measured by criteria contained in The Malcolm Baldrige National Quality Improvement Act and transformational leadership is measured by The Multifactor Leadership Questionnaire (MLQ). The population in this study is millennial employees in 33 Branch Offices of PT ASABRI (Persero) spread throughout Indonesia. Samples were taken using purposive sampling techniques so that as many as 134 millennial employees were selected as respondents to represent work units. The analysis technique used in the research is Structural Equation Modeling (SEM) with SmartPLS.3.0 software. The results showed that transformational leadership did not have a significant positive effect on organizational performance, transformational leadership had a significant positive effect on TQM implementation, and TQM implementation had a significant positive effect on organizational performance. In this study, it was also found that the implementation of TQM mediates the indirect influence between transformational leadership on organizational performance at PT ASABRI (Persero) Branch Offices. The results of this study contribute on the literary and practical side by providing a new understanding of the influence of transformational leadership on Organizational Performance through TQM Implementation in service companies.